Bank Holding Companies : Scope of Operation and Stock Ownership - Committee on Banking and Currency, House of Representatives (Washington : US Government Printing Office, 1963)
The report traces instances where stockholders of record appear among the top stockholders of more than one of the bank holding companies.
Committee of Banking and Currency, House of Representatives 88th congress
osc 10/7/17
Loans
Keywords: Bank Management